53BP1-ACLY-SLBP-coordinated activation of replication-dependent histone biogenesis maintains genomic integrity. Issue 3 (17th January 2022) - Wu, TingTing; Jun, Semo; Choi, Eun-Ji; Sun, Jiao; Yang, Eun-Bi; Lee, Hyun-Seo; Kim, Sang-Yong; Fahmi, Naima Ahmed; Jiang, Qibing; Zhang, Wei; Yong, Jeongsik; Lee, Jung-Hee; et al.
Abstract: p53-binding protein 1 (53BP1) regulates the DNA double-strand break (DSB) repair pathway and maintains genomic integrity. Here we found that 53BP1 functions as a molecular scaffold for the nucleoside diphosphate kinase-mediated phosphorylation of ATP-citrate lyase (ACLY) which enhances the ACLY activity. This functional association is critical for promoting global histone acetylation and subsequent transcriptome-wide alterations in gene expression. Specifically, expression of a replication-dependent histone biogenesis factor, stem-loop binding protein (SLBP), is dependent upon 53BP1-ACLY-controlled acetylation at the SLBP promoter. This chain of regulation events carried out by 53BP1, ACLY, and SLBP is crucial for both quantitative and qualitative histone biogenesis as well as for the preservation of genomic integrity. Collectively, our findings reveal a previously unknown role for 53BP1 in coordinating replication-dependent histone biogenesis and highlight a DNA repair-independent function in the maintenance of genomic stability through a regulatory network that includes ACLY and SLBP.